(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In the cultural life of the Kyrgyz people, the custom of waiting for guests is very important. They treated the animals specially appointed for the guests from slaughtering to drawing. In this article, it was written about the tradition of slaughtering a sheep waiting for a guest, dividing it into members and offering meat.